IOT Based Industry and Kitchen Monitoring and Controlling - Venkata Ratna Prabha K., Lavanya N., Sahithya K., M. Bhavani Prasad, Ravi Raja A., V. H. Prasad Reddy (International Journal of Advanced Science and Technology, 2020)
In present era of fast developing world, along with development, safety also plays an important role. The safety of workers and the industry and even at level of kitchen safety has to be considered. This type of safety measures can be done with the help of sensors to be addressed for high temperatures, gas leakages, fire/ smoke identification etc. The prototype of such safety device is designed by using sensors and controller circuit. The controller circuit receive inputs from sensors during bad incidents which in turn is sent from controller to the cloud, where in the cloud monitors and compares for automation and sends a SMS/alarm to the location, so that we can adjust or control the gas leakage, fire etc. as to be done. It is necessary to compete with the competitive world for minimizing the cost of the product along with the increase in quality to save the industries with minimum human monitoring for reliable functioning. This Paper proposes an IOT design system, and by the help of Raspberry -pi controller using Python in Web page.